2014
DOI: 10.1002/anie.201310239
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Efficient and Broadly Applicable Cationic Gold Catalyst

Abstract: Gold catalysts capable of promoting reactions at low-level loadings under mild conditions are the exception rather than the norm. We examined reactions where the regeneration of cationic gold catalyst (e.g., protodeauration) was the turnover limiting stage. By manipulating electron density on the substituents around phosphorus and introducing steric handles we designed a phosphine ligand that contains two electron-rich ortho-biphenyl groups and a cyclohexyl substituent. This ligand formed a gold complex that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(53 citation statements)
references
References 44 publications
0
53
0
Order By: Relevance
“…Although the factors influencing the catalyst deactivation are more complex, biaryl-decorated phosphine ligands were found to be beneficial in terms of catalyst stability. To this end, a very active gold(I) complex (III, Chart 1) 18 has been recently presented showing high efficiency at very low loadings (25 ppm) and relatively low temperatures (50 1C) in the gold-catalysed intermolecular hydroamination of alkynes. It is commonly accepted that for this type of catalysis, the protodeauration step 19 is ratedetermining, which should -in principle -be even more accelerated by increasing the donor-strength of the ligands.…”
mentioning
confidence: 99%
“…Although the factors influencing the catalyst deactivation are more complex, biaryl-decorated phosphine ligands were found to be beneficial in terms of catalyst stability. To this end, a very active gold(I) complex (III, Chart 1) 18 has been recently presented showing high efficiency at very low loadings (25 ppm) and relatively low temperatures (50 1C) in the gold-catalysed intermolecular hydroamination of alkynes. It is commonly accepted that for this type of catalysis, the protodeauration step 19 is ratedetermining, which should -in principle -be even more accelerated by increasing the donor-strength of the ligands.…”
mentioning
confidence: 99%
“…The need for a large excess of silver salt is not obvious, since our previous experiments had shown that [Au(ONf)( 3 b )] is already formed with approximately 2.5 equivalents of silver salt. However, it is well known that for many Au‐catalyzed reactions, a significant rate acceleration occurs in the presence of a large excess of silver salt . Based on these results, we conclude that the coordination of the alkyne to the gold and alkyne deprotonation are critical steps.…”
Section: Resultsmentioning
confidence: 83%
“…[40] Such reactions are very important in gold catalysis, often constituting the crucial activating step in numerousg old-catalyzed transformations. [41] Complexes such as [LAu(wca)] are generated in situ from [LAuX]( X = Cl, Br,I )t hrough silver salt metathesis involving precipitation of AgX, [42] but may also be isolateda nd then used in catalysis. [43] The nature of the anion and of the solvent, in which such reactions are carriedo ut, exert av ery significant influence on the formation of solvent-separated ions (vs. close ion-pairs) and consequently on catalytic activity.…”
Section: Gold Complexes With Weakly Coordinating Anionsmentioning
confidence: 99%
“…Since previously prepared mono-triazole-containing phosphines 1a and 1b were readily available to this programme of study, and as 1a was shown previously to have been among the superior ligands of the mono-triazole set in earlier palladiummediated Suzuki-Miyaura catalysis, the synthesis of gold(I) chloride complexes thereof was also attempted. The gold(I) chloride complex of 1a (11) was prepared by the aforementioned dimethyl sulfide ligand exchange reaction, in good yield (95%, 0.25 mmol scale). A single crystal XRD structure of 11 was obtained (Figure 10a), and closely matched (by visual inspection) the structure of 9a, with a 46.0%V bur .…”
Section: Gold(i) Chloride Complex Synthesis and Structural Analysismentioning
confidence: 99%